Equilibrium data for the cross-metathesis of methyl oleate with cinnamaldehyde - Nieres, Pablo Daniel (2018)
Here we present equilibrium data for the cross-metathesis of methyl oleate (MO) with cinnamaldehyde (CA) obtained experimentally from liquid-phase catalytic tests conducted at 323 K. The reaction was carried out in batch reactors, using different reactant molar ratios and the 2nd generation Ru Hoveyda-Grubbs complex as catalyst. Reaction mixtures at the equilibrium were analyzed by gas chromatography. Equilibrium constants were determined by assuming unitary activity coefficients for a cinnamaldehyde/methyl oleate equimolar ratio, and the validity of that approximation was evaluated by calculating the equilibrium conversions for different reactant molar ratios.